ANALISIS PENGHAMBAT PENERAPAN BUILDING INFORMATION MODELING (BIM) PADA KONTRAKTOR DI KOTA DENPASAR - Nodya Dharmastika; Gede Suranata, Putu; Cri Vinantya Laksmi, Ida Ayu (UKI Press, 2024)
ABSTRACT Technological developments in the construction industry have led to digitalization. One of them is the construction industry starting to implement Building Information Modeling (BIM). BIM is a system for managing information into building models in digital form. BIM processes input into information in the form of building modeling as an aid in the decision-making process at each stage of a construction project. In its application, BIM is still not optimal and has many obstacles. Of the 68 contractors in the city of Denpasar, only 3 contractors have used BIM in implementing their construction projects. Therefore, it is necessary to carry out a study to find out the factors that hinder the implementation of BIM among contractors in the city of Denpasar. The data collection method was carried out using a closed questionnaire which was distributed to 68 contractors in the city of Denpasar. The collected data was analyzed using Principal Component Analysis (PCA) factor analysis. The analysis carried out produced 3 factors that hindered the implementation of BIM in the city of Denpasar. These 3 factors include: difficulty in starting to implement BIM, high costs in implementing BIM, BIM is not a target for contractors. The third factor, namely that BIM is not the contractor's target, is the most dominant factor with the highest mean data value of 3.907. Keywords: Building Information Modeling (BIM); Obstacle Factor; Contractor; Factor Analysis